2002
DOI: 10.1002/mrm.10312
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance relaxivity of dendrimer‐linked nitroxides

Abstract: The relaxivity and bioreduction rates of eight dendrimer-linked nitroxides varying in the number of nitroxides per molecule were measured and the potential use of these compounds as MR contrast agents was demonstrated. The T 1 and T 2 relaxivities, measured at room temperature and 1.5 T, varied linearly with the number of nitroxides per molecule for compounds with up to 16 nitroxides per molecule. Fourth-generation polypropylenimide-(DAB) and third-generation polyamidoamine-(PAMAM) dendrimer-linked nitroxides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 37 publications
(123 reference statements)
0
70
1
Order By: Relevance
“…Interestingly, in a previous study of dendrimer-linked polynitroxides 12 in aqueous solution, the authors reported constant relaxivity on a per nitroxide basis. The apparent conflict between this result and the results of our study can be explained on the basis of known aggregation effects of nitroxide-labeled dendrimers in aqueous solution.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, in a previous study of dendrimer-linked polynitroxides 12 in aqueous solution, the authors reported constant relaxivity on a per nitroxide basis. The apparent conflict between this result and the results of our study can be explained on the basis of known aggregation effects of nitroxide-labeled dendrimers in aqueous solution.…”
Section: Discussionmentioning
confidence: 96%
“…The dendrimer framework has been shown to be advantageous in decreasing the bioreduction rate of nitroxide in vivo, an extremely rapid process which destroys the relaxation enhancer. 12 The potential of dendritic PREs in targeting specific organs has been investigated. 10,13,15 Our lab has studied stable nitroxide radicals for several years as ESR probes for surfaces and supramolecular assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies of the reduction of nitroxyl radicals (NR) have been reported (for reviews see [1,2]) because of the importance of this class of the compounds in biology and medicine where they are used as contrast agents for magnetic resonance imaging, MRI [3,4], spin labels [5], superoxide dismutase (SOD)-mimics [6], and antioxidants [7,8]. Chemical reduction of NR to EPR (electron paramagnetic resonance) -silent hydroxylamines (HA) in many cases is an unfavorable factor that significantly limits their applications in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the 1,3-alternate calix [4]arene nitroxide tetraradical and diradical were employed as model systems for the study of electron spin relaxation, [25] aimed at the development of functional paramagnetic contrast agents for electron paramagnetic resonance imaging (EPRI) and magnetic resonance imaging (MRI). [26], [27], [28], [29], & [30] These nitroxide polyradicals provide the probes for well-defi ned and moderately strong radical-radical interactions.…”
Section: Introductionmentioning
confidence: 99%